Proceedings of the International Workshop on Emerging Software as a Service and Analytics 2014
DOI: 10.5220/0004982800830088
|View full text |Cite
|
Sign up to set email alerts
|

Review and Analysis of Cloud Computing Quality of Experience

Abstract: Abstract. Cloud computing is gaining growing interest from industry, organizations and the research community. The technology promises many advantages in terms of cost saving by allowing organizations and users to remotely gain access to a huge pool of data storage and processing power. However, migrating services to cloud computing introduce new challenges in performance and service quality. Quality of service (QoS) is and has been used as a means of monitoring cloud service performance. However, QoS is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…A literature review and analysis on the current state of cloud computing has identified six key performance indicators (PKIs) that are essential for the proposed QoE framework [6]. The statistical analysis results have confirmed that the use of cloud QoE adoption has helped students to be more motivated for learning [6].…”
Section: Current Practice and Related Workmentioning
confidence: 93%
See 1 more Smart Citation
“…A literature review and analysis on the current state of cloud computing has identified six key performance indicators (PKIs) that are essential for the proposed QoE framework [6]. The statistical analysis results have confirmed that the use of cloud QoE adoption has helped students to be more motivated for learning [6].…”
Section: Current Practice and Related Workmentioning
confidence: 93%
“…A literature review and analysis on the current state of cloud computing has identified six key performance indicators (PKIs) that are essential for the proposed QoE framework [6]. The statistical analysis results have confirmed that the use of cloud QoE adoption has helped students to be more motivated for learning [6]. The typical representatives of real-time and on-demand multimedia content delivery systems require extensive research on Quality of Experience (QoE) estimation, which is based on selecting the appropriate services that will maximize the user's satisfaction with the delivered content.…”
Section: Current Practice and Related Workmentioning
confidence: 99%